Librarian Ethics: the Basic Attitude of Librarians at Medan Library and Archives Service is Based on the Indonesian Librarian Code of Ethics - Nur'aini, Nur'aini; Nasution, Laila Hadri (Universitas Pendidikan Indonesia, 2021)
This study aimed to determine the ethics of librarians on the basic attitudes of the Medan City Archives and Library Service. This research method uses descriptive research with a qualitative approach. The informants in this study were 4 librarians at the Medan City Archives and Library Service. The technique of taking informants using the purposive sampling technique. Data collection techniques through observation, interviews, and literature study. Data analysis in this study is carried on 3 (three) stages, namely data reduction, data presentation and conclusions. The results of this study show that the librarian of the Medan City Archives and Library Service carries out the task according to the visitors' needs by providing exemplary services and paying attention to the visitors' needs. Librarians strive to maintain competency excellence through various activities and are responsible for work in their fields. The librarian of the Medan City Library and Archives Service seeks to distinguish between personal attitudes and professional duties so that the services provided to users run well and avoid abuse of the profession in their duties.